1995
DOI: 10.1182/blood.v85.11.3077.bloodjournal85113077
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation after first remission induction treatment in multiple myeloma: a report of the French Registry on autologous transplantation in multiple myeloma

Abstract: Eighteen French centers reported 133 autologous stem cell transplantations performed after first remission induction in multiple myeloma. The source of stem cell was marrow (81 cases), blood (51 cases) or marrow plus blood (1 case). The immediate outcome after transplantation was 49 (37%) complete remissions (CRs) (13 maintained, 36 achieved), 61 (46%) partial remissions, 17 failures and 5 toxic deaths. With a median follow-up of 35 months, the median remission duration was 33 months, the median time to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(34 citation statements)
references
References 35 publications
2
30
1
1
Order By: Relevance
“…This analysis is one of the few reports of long-term outcome for myeloma patients treated with HDM, spanning just less than two decades. These results are comparable with, if not better than, outcomes in other published series with good long-term outcomes (median survivals of approximately 5 years) and a significant proportion of patients (35%) still alive at 10 years although a plateau in survival was not reached (Harousseau et al, 1995;Alegre et al, 1998). A number of studies have confirmed the superiority of HDM compared with conventional chemotherapy (Blade et al, 1996(Blade et al, , 2001Vesole et al, 1999) The Intergroupe Francais du Myelome 90 (Attal et al, 1996) was the first randomized trial showing better response rates, which translated into a survival benefit, and was subsequently confirmed in the larger Medical Research Council (MRC) VII study (Child et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…This analysis is one of the few reports of long-term outcome for myeloma patients treated with HDM, spanning just less than two decades. These results are comparable with, if not better than, outcomes in other published series with good long-term outcomes (median survivals of approximately 5 years) and a significant proportion of patients (35%) still alive at 10 years although a plateau in survival was not reached (Harousseau et al, 1995;Alegre et al, 1998). A number of studies have confirmed the superiority of HDM compared with conventional chemotherapy (Blade et al, 1996(Blade et al, , 2001Vesole et al, 1999) The Intergroupe Francais du Myelome 90 (Attal et al, 1996) was the first randomized trial showing better response rates, which translated into a survival benefit, and was subsequently confirmed in the larger Medical Research Council (MRC) VII study (Child et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…They were the first to demonstrate that high-dose melphalan can overcome drug resistance in patients refractory to conventional chemotherapy (McElwain & Powles, 1983). Introduction of stem cell support after high-dose chemotherapy markedly reduced the time of aplasia and, consequently, treatment-related mortality (TRM) decreased to less than 5% (Harousseau et al, 1995;Attal et al, 1996).…”
Section: Role Of High-dose Chemotherapy With Autologous Transplantatimentioning
confidence: 99%
“…2000). Several studies have demonstrated that high-dose chemotherapy combined with autologous hematopoietic stem cell transplantation can prolong overall survival, compared with conventional chemotherapy (Harousseau et al . 1995;Attal et al .…”
Section: Multiple Myelomamentioning
confidence: 99%